The Self‐Reference Effect on Memory in Early Childhood. Issue 2 (25th July 2013) - Cunningham, Sheila J.; Brebner, Joanne L.; Quinn, Francis; Turk, David J.
<x xml:space="preserve">Abstract</x> The self‐reference effect in memory is the advantage for information encoded about self, relative to other people. The early development of this effect was explored here using a concrete encoding paradigm. Trials comprised presentation of a self‐ or other‐image paired with a concrete object. In Study 1, 4‐ to 6‐year‐old children (N = 53) were asked in each trial whether the child pictured would like the object. Recognition memory showed an advantage for self‐paired objects. Study 2 (N = 55) replicated this finding in source memory. In Study 3 (N = 56), participants simply indicated object location. Again, recognition and source memory showed an advantage for self‐paired items. These findings are discussed with reference to mechanisms that ensure information of potential self‐relevance is reliably encoded.